A história do ensino da trompa em Recife e Olinda: possibilidades formativas para promover a inserção da trompa no frevo - Miranda, Osiel Lôbo de (2022)
This dissertation aims to identify the main factors that influenced the fact that the horn is not effectively inserted in the traditional practices and characteristics of the frevo and what is the relationship of this scenario with the formation of horn players working in the cities of Recife and Olinda. To achieve this general objective, the history of the horn in Pernambuco from 1700 to the present day will be addressed, contributing to an analysis of the context of teaching and practices at different times. In this context, characteristics of the teaching/learning processes, the germination of the frevo genre and its tributaries and historical aspects of the development of the construction of musical instruments inserted in the music band, especially the horn, were observed. A literature review was carried out on the history of the instrument and the music band in Pernambuco, and semi-structured interviews with conductors and composers from the frevo universe, as well as with Pernambuco horn teachers and professional horn players and students from the region. As for the interviews, it was possible to identify important themes related to the investigated context, namely the relationship between the horn and the saxhorn in the band; the multi-instrumentalist teacher; and the relationship of the interviewees with the frevístico repertoire. It was still possible to know the scenario of the history of the horn in Pernambuco, the types of instruments used at different times and their teaching. From the research carried out, it was possible to identify aspects that contributed to the horn not being effectively inserted in frevo and that indicate how the teaching of horn in Recife and Olinda may have influenced this situation.